Efficacy and safety of epsilon-aminohexanoic acid and tranexamic acid during posterior interbody fusion surgery - Ainiwaer, Dilixiati; Tuersun, Ayinuer; Li, Jiang; Li, Xiaomei (Frontiers in Surgery, 2025)
BackgroundTranexamic acid (TXA) is a proven effective and favored antifibrinolytic hemostatic drug, while epsilon-aminocaproic acid (EACA) has only recently been applied in the field of orthopedics. Few studies compare the efficacy of these two drugs in spinal surgery. We evaluated the hemostatic performance and safety of aminocaproic acid, and explored whether aminocaproic acid can be used as a substitute for TXA during posterior lumbar interbody fusion (PLIF) surgery, providing theoretical support for the flexible selection of hemostatic drugs during spinal surgery.MethodsWe conducted retrospective analysis of 180 patients with lumbar disc herniation, lumbar spinal stenosis, and lumbar spondylolisthesis, who had been admitted to the spinal surgery department of the Our hospital or The Sixth Affiliated Hospital of Xinjiang Medical University, between September 2021 and May 2023, and underwent PLIF. According to the types of hemostatic drugs used during the perioperative period, the patients were divided into two groups, namely, the EACA group (n = 86) and the TXA group (n = 94). The main outcome measures were total blood loss, total red blood cell loss, and transfusion volume/rate. Other outcome measures included length of hospital stay, hospitalization costs, deep vein thrombosis rate, and biochemical hematological indicators, specifically indicators related to anemia, nutrition, and coagulation.Results(1) The red blood cell width of the EACA group (43.94 ± 10.56) was significantly higher than that of the TXA group (40.45 ± 12.54), with a statistically significant difference (p < 0.05). (2) The postoperative total protein of the EACA group (56.17 ± 7.83) was significantly lower than that of the TXA group (59.3628 ± 6.73), with a statistically significant difference (p < 0.05). (3) The postoperative international normalized ratio of the EACA group (1.06 ± 0.14) was significantly lower than that of the TXA group (1.14 ± 0.13), with a statistically significant difference (p < 0.05). There was no statistically significant difference between the two groups in terms of other indicators.ConclusionThere was no significant difference in total blood loss, total red blood cell loss, transfusion volume/rate, postoperative hospitalization time, hospitalization costs, and surgical complications between the intravenous EACA and TXA groups during PLIF surgery. The two groups had similar hemostatic effects and safety outcomes. Therefore, when selecting antifibrinolytic drugs during PLIF surgery, EACA can be considered an alternative to TXA. However, large-scale, multicenter randomized controlled studies are still required to gauge its later-stage efficacy.